EFFICACY OF OMEPRAZOLE PLUS AMOXYCILLIN ERADICATING HELICOBACTER PYLORI - Ülkü SARITAŞ; Ahmet TEZEL; Mehmet KARAHAN; Uğur YILMAZ; Aysel ÜLKER; Gülay TEMUÇİN (Turkish Journal of Gastroenterology, 2020)
-